2013
DOI: 10.4236/ojped.2013.32016
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic changes due to human chorionic gonadotropin in the rat testis: Role of vascular endothelial growth factor

Abstract: Introduction: Human chorionic gonadotropin (hCG) has an important role in the regulation of reproductive system and a high capacity to stimulate angiogenesis by secretion of vascular endothelial growth factor (VEGF). It could be also used for medical treatment of cryptorchidism, as it stimulates Leydig cells to produce testosterone, but its use has been discussed. Aim of the study was to evaluate the testicular morphological changes due to cyclic administration of hCG possibly related to VEGF effect. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…B-mode ultrasonography is considered to be a more accurate, precise and reproducible method for measurement of TV in assessing testicular function and pubertal development [ 21 , 31 , 37 ]. An increase of TV recorded in this study after hCG injection was similar to those observed in men [ 14 ] as well as in rats [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…B-mode ultrasonography is considered to be a more accurate, precise and reproducible method for measurement of TV in assessing testicular function and pubertal development [ 21 , 31 , 37 ]. An increase of TV recorded in this study after hCG injection was similar to those observed in men [ 14 ] as well as in rats [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, there are reports which suggest that the hormonal stimulation in infancy may be damaging to the testes ( 39 ). It has been observed, in hCG-treated rats, a poor differentiation of the seminiferous epithelium, with high Leydig cell evidence and increased inter-tubular eosinophilic material ( 40 ). These experimental data emphasize the possible negative outcome of hormone therapy on germ cell line and its main action on Leydig cells.…”
Section: Hormonal and Surgical Treatment Of Cryptorchidismmentioning
confidence: 99%
“…The role of VEGF on spermatogenesis is unclear. Several findings have revealed several inhibitory effects of VEGF on spermatogenesis ( 40 , 41 ).…”
Section: Hormonal and Surgical Treatment Of Cryptorchidismmentioning
confidence: 99%
“…The combination of VEGF/VEGFR2 can inhibit apoptosis, promote endothelial cell proliferation, and improve vascular permeability [7][8][9]. Studies have also proved that VEGF and its receptor 2 were expressed in the epididymis, indicating that it may be may be involved in male reproduction [10][11][12].…”
Section: Introductionmentioning
confidence: 99%